Saving at tax time: Do additional retroactive savings opportunities increase retirement savings? - Kay Blaufus; Michael Milde; Marcel Schaefer (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
Using a series of experiments, we examine whether the additional opportunity to save retroactively for retirement at the time of tax filing increases overall retirement savings. Our findings show that introducing the additional savings opportunity at tax time increases the total savings rate by almost 5 percentage points. This positive effect holds regardless of whether retirement savings are taxed immediately (back-loaded pension plans) or deferred (front-loaded pension plans) or whether subjects expect back taxes or a tax refund. We show that the effect is not due to higher tax salience at tax time but that the additional offer to save nudges impulsive savings behavior. Policymakers may thus consider the introduction of an additional savings opportunity at tax time as a policy tool to encourage retirement savings. In addition, policymakers should consider the advantage of immediate over deferred taxation in increasing retirement savings. We show that the savings gap between immediate and deferred taxation found in previous studies can expand further if savings are additionally allowed at tax filing.
Keywords: D9; D14; D15; G51; H31; 330; Retirement savings; tax incentives; impulsive savings; tax salience; nudging; deferred taxa-tion